GENDER DIFFERENCES IN TEACHER QUESTIONING STRATEGIES: A CASE STUDY AT SMKS PASUNDAN 1 CIANJUR - Nia Kurniawati; Neni Suryani (Indonesian EFL Journal, 2024)
This study investigates the questioning strategies of male and female English teachers in EFL classrooms at SMKS Pasundan 1 Cianjur. Using a qualitative descriptive method and a case study approach, data were collected through observations, questionnaires, and interviews. The findings reveal that both genders use diverse questioning strategies to enhance classroom interaction, incorporating questions at the beginning, middle, and end of lessons. Furthermore, both genders use three main types of questions: procedural, convergent, and divergent. However, significant differences exist in the frequency and types of questions used. This research highlights how gender dynamics influence teaching methods and student engagement, providing valuable insights for improving EFL education.Keywords: Teacher’s Questions; Types of Questioning Strategies; Classroom Interaction; EFL Classroom; Dender Differences